The relationship between isokinetic trunk and upper limb muscle strength and respiratory function and respiratory muscle strength: a cross-sectional study - Balci, A.; Akinoglu, B.; Kocahan, T.; Hasanoglu, A. (Medicina dello Sport, 2020)
BACKGROUND: The relationship between respiratory functions and skeletal muscle strength is important because each contributes to athletic performance alone. In previous studies, while the relationship between the trunk and lower limb muscle strength and respiratory functions was investigated, the number of studies on the relationship between the upper limb and respiratory functions is limited. The aim of the study was to determine the relationship between the trunk and upper limb isokinetic muscle strength and respiratory functions and respiratory muscle strength. METHODS: A total of 233 (145 males, 88 females) elite athletes were included in the study. Pulmonary function tests, shoulder horizontal abduction/adduction isokinetic muscle strength measurement, and trunk flexion/extension-right/left rotation isokinetic muscle strength measurements were performed on 3 different days to the athletes. The obtained data were separated due to gender and compared with the Independent Samples T-test or Mann Whitney U Test. The relationship between parameters was evaluated by Pearson or Spearman Correlation Tests. RESULTS: As a result of statistical analysis, it was determined that all strength and respiratory function parameters differ between genders, and all parameters were found higher in the male athletes (P<0.05). Weak/moderate/strong correlation (r=0.130-0.801) was found between trunk and shoulder isokinetic muscle strength with pulmonary function tests. Weak/medium correlation was found between trunk and shoulder isokinetic muscle strength with respiratory muscle strength measurements (r=0.167-0.577). CONCLUSIONS: As a result of the study, it was observed that the upper limb muscles were associated with respiratory functions as well as the trunk muscles in athletes. This result suggests that the upper limb muscles may contribute to performance by affecting respiratory functions. Another important result of the study is that the relationship between the trunk and limb muscles with respiratory muscle strength is not as strong as the relationship with respiratory functions. This result is to reveal the idea that respiratory muscles specific training may have a positive effect on respiratory functions and sports performance.